DEVELOPING NEXT GENERATION SCIENCE STANDARDS (NGSS) ORIENTED-BASED ETHNOSCIENCE TEACHING MATERIALS: IMPROVING CONSTRUCTING EXPLANATION AND DESIGNING SOLUTIONS (CEDs) SKILLS FOR PROSPECTIVE ELEMENTARY SCHOOL TEACHERS - Duhita Savira Wardani; Rahman Rahman; Zaqiyah Lailatul Farihah; Ryan Dwi Puspita (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to produce teaching materials oriented to Next Generation Science Standards (NGSS) that can improve the Construction Explanation and Designing Solutions (CEDs) skills of elementary school teacher candidates. This study uses the development research method (RnD) adapted from Borg & Gall. The 10 Borg&Gall development procedures were then modified into 8 stages which were adapted to the conditions in the field. The results of the study show that NGSS-oriented teaching materials are appropriate for use in learning with valid, practical, and effective criteria. The validation results obtained from the average value of the teaching material expert validator and learning media show that the teaching material is considered valid both in terms of construct and content. The results of observing the activity of lecturers and students increasing at each meeting indicate that practical teaching materials are applied in learning, as well as the results of student CEDs skills tests indicating that teaching materials are effective for improving the CEDs skills of prospective teacher students. The implication of this research is that the use of appropriate methods can affect the achievement of CEDs ability of prospective teachers to be able to present various alternative solutions to problems. The suggestions for further research are to develop NGSS-oriented teaching materials for elementary school students.